Vigilância epidemiológica da COVID 19 – Região GVE XXI – Presidente Prudente, São Paulo - Lagisck , Ana Paula; de Moraes, Marco Antonio; Matsura Shirassu, Mirian; Bouças Ribeiro, Adriana; Cardoso de Paula, Regiane; Lang D’Agostini, Tatiana; de A Pititto, Bianca; Melo, Karla (BEPA. Boletim Epidemiológico Paulista, 2020)
.